Airport Competition in the Czech Republic and Neighboring Areas - Heřmánková, Lenka; Melichar, Vlastimil (STEF92 Technology Ltd., 2016)
Competition between airports increased rapidly since the deregulation of the intra European air transport market in 1997. Currently the passengers have much wider choice to select the departure airport and route as well, which leads to airport substitution. Phenomenon, that airports should take into consider is called Airport traffic leakage. It represents the situation when decrease of the volume of passenger occurs on small airports at the expense of large airports with extensive services. The aim of this paper is to describe the competitive position of airports in the Czech Republic and its neighboring areas by using various analyzes. Commonly used method how to measure competition between airports is to create lists of airports ranked by total number of transported passengers or cargo and number of aircraft movements at the airport. More sophisticated method used in the paper is based on geographical overlaps between airport catchment areas by using isochrones maps. Isochrones maps gave us a rough estimation of what airports in the country might compete with each other based on travel times between airports. To validate the dependence between transportation performances of various airports was also used correlation analysis because it allowed verification of the dependence on the basis of numerical calculations, and therefore gave more reliable results than other methods.
Konkurence letišť v České republice a v sousedních oblastech
Keywords: airport competition; catchment areas; correlation analysis; airport traffic leakage; konkurence letišť; dojezdové oblasti; korelační analýza; úbytek letištního provozu